PENYULUHAN PENCEGAHAN DIABETES MELITUS DI LEMBAGA PEMASYARAKATAN LABUHAN DELI - Situmorang, Novrina; Hutasoit, Eka Samuel P.; Situmeang, Ivonne Ruth V. O.; Br. Sinaga, Inda M. H.; L. Tobing, Paul S. M.; Marpaung, Alexander P.; Simanjuntak, Maestro B. U.; Siregar, Romatiur Marantha B. (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Community Service (PKM) conducted by the Faculty of Medicine at the Indonesian Methodist University provides counseling on the benefits of basic immunization. Community Service was held on July 28 2023 at the Labuhan Deli Correctional Institution, Medan Labuhan District, Medan City, North Sumatra. Lectures, discussions and motivation are used as orientation methods. A question and answer discussion was held with the aim of gaining insight and understanding from the employees and residents of the Labuhan Deli correctional institution. The result of this outreach is that employees and residents of the Labuhan Deli Penitentiary have knowledge about Diabetes Mellitus, its symptoms, risk factors, and the complications it causes so that employees and the community can carry out prevention as early as possible.